Perception and practices pertaining to menstruation among adolescent girls - Mekle, Dinesh; Rathore, Richa; Dixit, Jagdamba; Kapoor, Anju (Pediatric Review: International Journal of Pediatric Research, 2020)
Objective: To assess the perceptions and practices related to menstruation among adolescent girls of rural and urban schools. Methodology: This was a cross-sectional study conducted at selected government as well as private schools of rural and urban areas. Adolescent girls of age group between 10-17 years who have attained menarche were enrolled in the study. Data regarding socio-demographic profile, knowledge, practices, and perception related to menstruation was obtained using a predefined questionnaire. Results: The study enrolled 350 girls from rural and 350 girls from urban schools. Maternal education was found to be higher in an urban setting as compared to the rural setting. Genital hygiene practices and usage of the sanitary pad were significantly better amongst urban girls as compared to rural girls (p<0.01). About 35% of girls in the urban setting and 26% of rural settings were mentally prepared for menarche. Most of the girls were forced to follow various types of restrictions like going to the temple, entering into the kitchen, etc during menstruation in both the settings. Conclusion: There is poor mental preparedness for menstruation before attaining menarche, poor hygienic practices, and negative perception regarding menstruation among adolescent girls. This requires educational intervention involving both young girls and their mothers.